COMPARISON OF ECOENZYME QUALITY BASED ON ORGANOLEPTIC TEST RESULTS ON VARIOUS ORGANIC FRUIT AND VEGETABLE MATERIALS - Yuliastuti; Amin, Nurdin (Barkah Publishing, 2025)
Eco-enzyme is a multifunctional liquid produced from the fermentation of organic waste. This study aims to compare the quality of the eco-enzyme in various organic materials (fruits and vegetables). This study includes qualitative and quantitative observations. Qualitative observations include organoleptic tests, including aroma, color, and texture. Quantitative observations include measurements of pH, TSS, and TDS levels. The research data shows that the eco-enzyme with pineapple material obtained the highest volume of 36.95%. Meanwhile, cabbage leaves and onion skins showed the best quality in terms of clarity, with the lowest TSS value of 10-13 mg/L. The combination of fruit skins produced an eco-enzyme with the highest mineral content, namely a TDS concentration of 2,755 mg/L, but with a lower fermentation rate at pH 5. The results obtained indicate that each material has its own advantages in certain test parameters